2004
DOI: 10.1111/j.1349-7006.2004.tb03242.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel mouse model of rectal cancer established by orthotopic implantation of colon cancer cells

Abstract: A novel intraluminal colon tumor model was established in mice by intrarectal instillation of colon cancer cells followed by shortterm induction of colitis by an irritant agent. Male BALB/c mice were fed a diet containing 3% (w/w) dextran sulfate sodium (DSS) for 7 days to induce colitis, and colon 26 cells (1-2 × × × ×10 6 cells/mouse) were infused intrarectally after the mice had been deprived of food for the last 18 h of DSS treatment. The tumor incidence (%) and size (mean volume ± ± ± ±SD, mm 3 ) at the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 25 publications
0
24
0
1
Order By: Relevance
“…Limited numbers of studies describe feasible, practical and reliable experimental models that mimic both primary and metastatic colorectal cancer in the same animal [2,[4][5][6][7]. In the present studies, subserosal colorectal tumor models were developed in mice, in parallel with protocols aimed at provoking dissemination of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited numbers of studies describe feasible, practical and reliable experimental models that mimic both primary and metastatic colorectal cancer in the same animal [2,[4][5][6][7]. In the present studies, subserosal colorectal tumor models were developed in mice, in parallel with protocols aimed at provoking dissemination of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Although significant improvements in care in patients with early disease have followed clinical advances with better screening, diagnosis and treatment modalities, pre-existing tumor growth and metastatic spread still limit long-term patient survival [1,2]. Targeted surgical resection, in combination with cutting edge type interventions, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that colon cancer can be established orthotopically after the induction of colitis [3]. The enema model in these studies, however, requires an initial induction of colitis to allow invasion of…”
Section: Resultsmentioning
confidence: 99%
“…This orthotopic model requires a surgical incision for injection of cancer cells. Therefore, an initial immune response with this surgical model would limit the feasibility and reliability of future research goals of measuring immune responses after open or minimally invasive cecal resections.Previous studies have demonstrated that colon cancer can be established orthotopically after the induction of colitis [3]. The enema model in these studies, however, requires an initial induction of colitis to allow invasion of…”
mentioning
confidence: 99%
“…11 The use of a 3D matrix for orthotopic implantation of various tumor cell types has precedent using a reconstituted basement membrane preparation, Matrigel, where enhanced tumor growth and increased metastasis are observed relative to implantation of cells alone. 12,[13][14][15] Matrigel has severe technical limitations, including its lot-to-lot variability and difficulty in handling during injection of cell suspensions. An injectable, in situ gelling matrix that can be easily manipulated in the laboratory would be desirable for pancreas implantation of PA tumor cells.…”
Section: Introductionmentioning
confidence: 99%